Expanding Technology Acceptance Model 3 Use Innovation Diffusion Theory on Accounting Learning During Pandemic: Insight from Indonesia - Kharisa Rachmi Khoirunisa; Sony Warsono; Aryan Danil Mirza. BR (The Indonesian Journal of Accounting Research, 2023)
This study adds value to the existing limited literature on TAM 3 model by using Innovation Diffusion Theory to analyze how the intention to use Sidek Akuntamatika, a platform for online practicum learning among accounting lectures and teachers in Indonesia during the recent Covid-19 pandemic. We surveyed 150 accounting lecturers and teachers who signed up for the e-Workshop on Service, Trade, and Manufacturing Accounting and completed the corresponding online practicum. We use Structural Equation Modeling (SEM) as a data analysis method and WARP-PLS version 7.0. as the analytical tool. The findings show that people's opinions of Sidek Akuntamatika improve if the organization can demonstrate its results and its brand is viewed favorably. Then, perceived external control, self-confidence, and playfulness have also been identified as factors that precede a person's estimation of a task's difficulty. This study also found that perceived usefulness and perceived ease of use positively influenced intent to use. As the "innovation diffusion" theory would have it, compatibility is crucial in determining whether people plan to adopt the Sidek Akuntamatika. Government and stakeholders in education need to encourage learning innovations, especially to solve learning activity problems due to the Covid-19 pandemic. On the other hand, lecturers or teachers at the forefront of the transfer of knowledge in accounting learning need to pay more attention to choosing the best learning tool to enhance students' intention in studying.